Perbandingan Kesatuan Sekerja Dan Pendemokrasian Di Borneo Malaysia Dan Borneo Indonesia: Kajian Kes Di Sektor Minyak Dan Gas, Perkayuan Dan Kelapa Sawit - Syed Annuar, Sharifah Nursyahidah (2021)
Generally, trade unions in Malaysia have been experiencing gradual growth despite functioning, in a semi-authoritarian political climate. Meanwhile, the total number of trade unions and their membership have been declining in Indonesia despite its robust democracy in the post-1998 era. However, studies on trade unions and labour movement tend to be predominantly concentrated in Peninsular Malaysia and Java. Therefore, this study aims to understand the comparison of trade unions in other parts of Malaysia and Indonesia, namely Malaysian Borneo and Indonesian Borneo. Both Malaysian Borneo and Indonesian Borneo are almost similar in terms of their demography and geography. Preliminary observation indicates that there are different patterns in the national trend. Trade unions in Malaysian Borneo deviate from the trend in Peninsular Malaysia, whilst trade unions in Indonesian Borneo follow the trend in Java. To better understand the difference in trend, this study focuses on case studies based on three main and similar economic sectors in Borneo: oil and gas, timber, and palm oil. The study areas are Bintulu, Sipitang and Tawau (Malaysian Borneo) and Balikpapan, Banjarmasin and Kotabaru (Indonesian Borneo). This study also conducted semi-structured interviews with six trade unions, two trade union congresses, one trade union confederation, academics, authorities, and others. Hofstede’s national culture, Hyman’s functions of the State, and democratisation concept by Acemoglu and Robinson form the conceptual framework for this study